A Review of Islamic Law on the Practice of Ijarah Muntahiyah Bittamlik Contracts in Islamic Banking in Indonesia - Suci Ramadania; Winda Syafitri; Shindy Cahyana; Tania Prasadila; Nazli Aisyah Amin; Sindi Agustiana; Muhammad Nur Iqbal (Jurnal Ekonomi, Akuntasi dan manajemen Indonesia (JEAMI), 2026)
Ijarah Muntahiyah Bittamlik (IMBT) is a financing product in Islamic banking in Indonesia that combines the concept of leasing (ijarah) with the option of transferring ownership (tamlik) at the end of the contract period. This study aims to examine the legal basis, operational mechanisms, sharia compliance, and obstacles in implementing IMBT, based on DSN-MUI Fatwa Number 27 of 2002 and the Compilation of Sharia Economic Law. In practice, the bank acts as the asset owner and then leases the asset to the customer. At the end of the lease period, there is an option to transfer ownership to the customer through a sale or grant mechanism. The study results indicate that IMBT generally complies with sharia requirements. However, its implementation still faces several challenges, such as low sharia financial literacy among customers, operational complexity, and the risk of problematic financing. Efforts to address this are carried out through strengthening regulations, restructuring contracts, and utilizing ta'zir funds for the qardhul hasan program. This study emphasizes the importance of improving Islamic financial literacy and modernizing banking operational systems to optimize IMBT's contribution to the development of an inclusive and sustainable Islamic economy.